REDUCING THE INTENSITY OF TAKEAWAY PULVERIZED COAL BY USING SPECIAL SOLUTION - Biliaiev, M. M.; Karpo, A. A.; Yakubovska, Z. M. (Science and Transport Progress, 2017)
Purpose. The article is aimed: 1) to develop the coal coating solution in open railway cars or to cover coal piles to minimize the coal dust losses; 2) creating a mathematical model of the process of the solution feeding to the surface of coal. Methodology. To solve this problem, it was developed a special solution containing cheap industrial wastes and semiproducts of chemical industries. It was conducted a physical experiment to assess the intensity of coal dust loss when using the developed solution. A mathematical model based on the use of the motion equations of the ideal fluid and mass transfer was developed. The developed numerical models are the basis of the application program package created for assessing the quality of processing the coal surface by special solution. Findings. The results of the conducted physical experiment to assess the magnitude of the coal dust loss on the model of the coal pile in the processing of its surface with a special solution and without processing are presented in the article. It is shown that the application of the proposed solution for surface processing of coal can significantly reduce the coal dust loss. This makes it possible to reduce the amount of economic losses and reduce the level of air dust pollution in work areas. The results of computational experiments carried out on the basis of the constructed numerical models are presented in the article. Originality. Authors proposed a new solution for the coal surface processing in order to minimize the removal of pulverized coal from the coal pile, which substantially reduces the coal losses. There were created numerical models to take into account the relevant factors influencing the solution dispersion process in the atmosphere from coal processing in gondola cars. Practical value. Solution, proposed in the article has a low price, because it can be created on the basis of industrial production wastes. Application of this solution can significantly reduce the intensity of coal dust losses from the surface of the coal pile. There were considered effective numerical models «diagnostic models» for rapid calculation of cargo processing in gondola cars with the solution. The models may be used in developing strategies of solution feeding to the cargo surface at various atmospheric conditions. The constructed numerical models can be used for scientific substantiation of the parameters of cargo processing with various forms of its surfaces in the gondola car.